2020
DOI: 10.5194/acp-2020-429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct aerosol effects on cloud-to-ground lightning in the plateau and basin regions of Sichuan, Southwest China

Abstract: Abstract. The joint effects of aerosol, thermodynamic, and cloud-related factors on cloud-to-ground lightning in Sichuan were investigated by a comprehensive analysis of ground measurements made from 2005 to 2017 in combination with reanalysis data. Data include aerosol optical depth, cloud-to-ground (CG) lightning density, convective available potential energy (CAPE), mid-level relative humidity, lower- to mid-tropospheric vertical wind shear, cloud-base height, total column liquid water (TCLW), and total col… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
1
6
0
1
Order By: Relevance
“…The correlation between CBH and TCLW with lightning is reversed in plateau and basin regions. In the plateau region, the high TCLW and low CBH indicate that more liquid water is transported to the mixed‐phase region due to the compression effect of plateau topography on cloud, which is favourable for the noninductive electrification process, while, in the basin region, high TCLW and low CBH indicate strong warm‐phase process, which is unfavourable to ice‐phase process and lightning process (Zhao et al ., 2020). The strong convective intensity and ice‐phase process are favourable to the noninductive electrification of collision–separation between ice particles in the mixed‐phase region, which is favourable to the generation and development of lightning activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between CBH and TCLW with lightning is reversed in plateau and basin regions. In the plateau region, the high TCLW and low CBH indicate that more liquid water is transported to the mixed‐phase region due to the compression effect of plateau topography on cloud, which is favourable for the noninductive electrification process, while, in the basin region, high TCLW and low CBH indicate strong warm‐phase process, which is unfavourable to ice‐phase process and lightning process (Zhao et al ., 2020). The strong convective intensity and ice‐phase process are favourable to the noninductive electrification of collision–separation between ice particles in the mixed‐phase region, which is favourable to the generation and development of lightning activity.…”
Section: Resultsmentioning
confidence: 99%
“…In North China, large CAPE is more favourable for mesoscale convective systems to produce high lightning frequency and precipitation rate (Liu et al ., 2011; Xia et al ., 2018). The lightning flash rate in western Sichuan Plateau is significantly lower than that in Sichuan Basin, while the ratio of positive lightning in the plateau region is higher than that in the basin, which may be related to spatial differences in CAPE, mid‐level relative humidity, and cloud properties (Zhao et al ., 2020, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The WWLLN strokes and pulses are combined with ENTLN into one dataset (ENGLN) within 10 km and 0.7 s as mentioned in Virts and Goodman (2020). To increase the lightning data coverage in our study, the CG flashes of ENGLN and CNLDN datasets are combined using spatial and temporal clustering criteria of 10 km and 0.5 s (Zhao et al, 2020). Merging these three datasets should provide a sufficiently high CG flash detection efficiency for this analysis.…”
Section: Lightning Datamentioning
confidence: 99%
“…Zhao et al. (2020) indicated that increased aerosols inhibit lightning activity in the basin through the radiative effect based on a ground‐based measurement in combination with reanalysis data. By means of numerical simulation, Fan et al.…”
Section: Introductionmentioning
confidence: 99%